A constructional analysis of obligatory XVS syntactic structures - Prado-Alonso, Carlos (Adam Mickiewicz University, 2016)
The analysis of obligatory or formulaic XVS structures — as in “Here comes the sun” or “Now is the time to solve our problems” — has been neglected in the literature since it has been argued that there seems to be no linguistic variation involved in the use of these types of syntactic constructions. Here, I defend the view that obligatory XVS structures are productive, highly structured constructions which are worthy of serious linguistic investigation. On the basis of a corpus-based analysis of written and spoken texts, it is argued that the different obligatory XVS types distinguished in the literature are clear instances of constructions as understood in the Construction Grammar framework. Despite their formal and functional dissimilarities, the article shows that these XVS structures still relate to one another in systematic and predictable ways, and are in fact grouped in relation to a unit in the schematic network which is naturally most salient — the prototype — and form with it a family of nodes which are extensions from the prototype — in the system. In sum, the analysis here will show that obligatory XVS structures are constructions which form an interconnected, structured system or network and are best understood with reference to different forms of inheritance.
Keywords: word-order; XVS constructions; radial; prototype; corpus linguistics